Digital signal processing systems implementation techniques - Leondes, Cornelius T. (Control and dynamic systems;)
This volume on implementation techniques in digital signal processing systems clearly reveals the significance and power of the techniques that are available, and with further development, the essential role they will play as applied to a wide variety of areas. The authors are all to highly commended for their splendid contributors to this volume, which will provide a significant and unique international reference source for students, research workers, practicing engineers, and others for years to come.